Answer:
15 yd = 45 ft because :
Step-by-step explanation:
You have to multiply the length by 3.
1 yd = 3 ft.
15 x 3 = 45.
Hope this helps,
Davinia.
Answer:
56.25 ft
Step-by-step explanation:
It is simple, since it is a square the sides are all the same length so you take A=area and divide it by four= h or w or l (height, width, length) so
225/4=56.25
Answer:
x=2
y = 0
Step-by-step explanation:
3x + y = 6 -------------(i)
5x - 2y = 10 -------------(ii)
Multiply (i) by 2 ===> 6x +2y = 12
(ii) ===> <u> 5x - 2y = 10</u>
add ============> 11x = 22
x = 22/11
x = 2
Substitute x = 2 in (i)
3*2 + y = 6
6 + y = 6
y = 6 - 6
y = 0
These triangles are congruent by AAS condition hence the statement is true